The changing of occlusal plane inclination in Class II malocclusion - Nelvi Yohana; Siti Bahirrah; N. Nazruddin (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Camouflage treatment of skeletal Class II malocclusion can be performed using extraction or non-extraction techniques. These treatments can cause changes in occlusal plane. Steep occlusal plane during corrective treatment generally relapses after active orthodontic treatment, resulting in unstable interdigitation. Purpose: This study aims to determine and evaluate changes in occlusal plane inclination in skeletal Class II malocclusion cases using extraction or non-extraction techniques of the permanent maxillary first premolar. Methods: The samples consisted of initial and final cephalometry of 40 adult patients with skeletal Class II malocclusion divided into two groups, namely extraction of the permanent maxillary first premolar and non-extraction group. The inclination of occlusal planes in both groups was measured using the ImageJ software, then the factors associated with these changes were observed. Furthermore, the occlusal plane inclination was compared between the extraction and non-extraction groups by using t-test. Results: The occlusal plane inclination in the non-extraction group increased slightly, while the inclination in the extraction group increased significantly (p = 0.017, p-value < 0.05). However, there was no correlation found in the occlusal plane inclination between the extraction and non-extraction groups (p = 0.07, p-value < 0.05). Conclusion: Class II malocclusion correction with either extraction or non-extraction of the maxillary first premolar increased the inclination of the occlusal plane. This study indicated that control of the occlusal plane inclination is highly essential.